การป้องกันปัญหาอาชญากรรมสิ่งแวดล้อม: กรณีศึกษาผลกระทบจากมลพิษทางอากาศในนิคมอุตสาหกรรมมาบตาพุด - กรณัฏฐ์ อัครธนบูลย์ (จุฬาลงกรณ์มหาวิทยาลัย, 2020)
This study emphasized studying problems and impacts of air pollution, causes, and factors causing air pollution in an environmental criminology perspective in order to propose solutions to prevent and solve environmental crime especially, the air pollution problem in the Map Ta Phut Industrial Estate efficiently and sustainably. The researcher conducted the documentary research and in-depth interviews among 6 specific sample groups with 24 samples included the group of people in Map Ta Phut municipality, leaders and representatives of the communities surrounding the Map Ta Phut Industrial Estate, government agencies and state enterprises, independent scholars, non-governmental organizations (NGOs), and criminal justice personnel. The findings revealed as follows: the problems and impacts of air pollution affecting  (1)  the health of people as they are still at risk of respiratory disease, cancer and other disorders due to inhalation of air pollution and (2) the environment, which from air quality measurements found that there are still pollutants emitted from industrial plants continuously and is higher than the standard set In particular, some types of volatile organic compounds (VOCs).  The causes and factors resulting in the air pollution problems were a result of (1) the economic development is unbalanced with the environment or ecosystem, (2)   the government and related agencies management do not comply with the principles of environmental governance, (3)  the measures and systems for measuring air quality do not reflect facts, and (4) the law enforcement and penalties are unclear. The causes of wrongdoing among the stakeholders in the environmental criminology perspective included  (1) the government conducts economic policies damaging the environment and affecting the health of the people as direct and indirect victims, (2) the entrepreneurs or polluters are not aware that they are committing the environmental crime or intentionally committing it, as it benefits the loopholes of the law rather than the penalties, (3) the affected persons or the direct victims are human, who have been damaged by environmental crimes both in the short and long term since it is difficult to prove themselves and arrest the perpetrators, and (4) the general public or the indirect humans as victims lack knowledge and care for environmental problems since they did not realize the right to live in a good environment. As the solutions to prevent and solve air pollution problems, it was found that the government should pay more attention to improving and integrating environmental laws with clear enforcement and penalties in conjunction with promoting industrial factories to be aware of caring for the environment. This can be classified into concrete by (1) coordinating cooperation between government agencies, the private sector and the public sector in seriously dealing with air pollution problems in the Map Ta Phut Industrial Estate. (2) Apply engineering principles to solving air pollution problems along with standard control of polluted air emissions. (3) There is a management system for solving both short and long term air pollution problems.